Moo-ving livestock and climate up the agenda at COP 28 - Cramer, Laura K.; Flintan, Fiona E. (ILRI, 2023)
The 28th Conference of Parties (COP28) of the United Nations Framework Convention on Climate Change (UNFCCC) was held in Dubai, UAE from 30th November to 12th December. The Livestock and Climate Initiative of One CGIAR participated in a multitude of side events to moving livestock and climate up the agenda both in terms of mitigating the impact of livestock on the climate and supporting livestock farmers to adapt to climate change.